Prevalensi Kematian Ibu Dan Faktor Risiko Yang Mempengaruhinya - Ahmad, Zul Fikar; Nurdin, St. Surya Indah (Madu : Jurnal Kesehatan, 2024)
Maternal mortality is one of the significant maternal and child health problems in Indonesia. Maternal death not only affects the quality of life of the baby but also the family. This study aims to research the prevalence and risk factors for high maternal mortality. The type of research used was analytical observational with a case-control study design. The sample size of cases and controls used a ratio of 1:2. The instrument used was a questionnaire. Odd Ratio assessed the magnitude of risk. Anaemia during pregnancy, type of delivery, pregnancy complications, delivery complications, and delay in referral were found to have a statistically significant association with maternal mortality. Maternal education, maternal age, family socioeconomics, parity, pregnancy spacing, history of miscarriage, ANC examination, nutritional status of pregnant women, history of maternal illness, puerperal complications, access to health services, clean and healthy living behaviour, and exposure to cigarette smoke were found to have no statistically significant association with maternal mortality. In the future, it is necessary to improve facilities and infrastructure to support maternal and neonatal emergency services.